2022
DOI: 10.3390/cells11060986
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Signaling in Lung Fibrosis

Abstract: In this review article, we will first provide a brief overview of the ErbB receptor–ligand system and its importance in developmental and physiological processes. We will then review the literature regarding the role of ErbB receptors and their ligands in the maladaptive remodeling of lung tissue, with special emphasis on idiopathic pulmonary fibrosis (IPF). Here we will focus on the pathways and cellular processes contributing to epithelial–mesenchymal miscommunication seen in this pathology. We will also pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 109 publications
(146 reference statements)
0
20
0
Order By: Relevance
“…On the basis of these findings, we speculate that ZBM can also exert antipulmonary fibrosis effects through the JAK/STAT signaling axis. Interestingly, the epidermal growth factor receptor (EGFR), a member of the ErbB tyrosine kinase receptor family, was shown to participate in wound healing and tissue regeneration by activating downstream PI3K/AKT, MAPK/ERK, and STAT signaling pathways [ 66 ]. In our study, we found that ZBM also significantly modulated the expression of EGFR and SRC, a nonreceptor tyrosine kinase that activates STAT3 and trans-activates EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these findings, we speculate that ZBM can also exert antipulmonary fibrosis effects through the JAK/STAT signaling axis. Interestingly, the epidermal growth factor receptor (EGFR), a member of the ErbB tyrosine kinase receptor family, was shown to participate in wound healing and tissue regeneration by activating downstream PI3K/AKT, MAPK/ERK, and STAT signaling pathways [ 66 ]. In our study, we found that ZBM also significantly modulated the expression of EGFR and SRC, a nonreceptor tyrosine kinase that activates STAT3 and trans-activates EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…6, F and G). Given the evidence for aberrant EGFR signaling in lung fibrosis (50-52) and the differential expression of both EGFR receptors and ligands in the cluster B cells, the sensitivity of cluster B cells to EGFR inhibitors may provide a cellular mechanism for the efficacy of such drugs in model systems (51)(52)(53)(54)(55)(56).…”
Section: Ipf Stem Cell Variants In Small-molecule Screensmentioning
confidence: 99%
“…The contribution of airway epithelial cells to the development of IPF is supported by multiple lines of evidence, including the cellular composition and morphological alterations of IPF airways, strong associations between the MUC5B promoter rs35705950 polymorphism and the risk of IPF, and the bronchiolization of distal airspaces in IPF lungs. The contribution of airway epithelial cells to IPF pathogenesis is also addressed by Schramm et al, who discuss the role of the ErbB receptor–ligand system in lung fibrosis [ 15 ]. Intriguingly, the deregulation of the ErbB receptor-ligand axis is mainly observed in the regions of alveolar bronchiolization.…”
mentioning
confidence: 99%
“…This underlies the pivotal role of ErbB receptors in the reprogramming of airway epithelial cells, and thereby honeycomb cyst formation and IPF progression. The authors of this comprehensive review emphasize the dual role of ErbB receptors and their ligands in lung fibrosis and indicate the need to elaborately characterize the dynamics and causal flows in the ErbB signaling networks in acute versus chronic lung injury [ 15 ].…”
mentioning
confidence: 99%